Structural Changes in the Economy of Cross-Border Regions of Russia and China - Zabelina, Irina; Klevakina, Ekaterina (International Journal of Economics and Financial Issues, 2016)
The article examines the structural changes in the Russian and Chinese regions involved in the processes of cross-border cooperation. The resulting quantitative assessments indicate that the most noticeable structural changes in all Russian regions took place during the period from 2009 to 2013. At that, their value exceeds the changes observed in average in the RF as well as in neighboring border regions of China. In the Chinese provinces, significant structural changes are observed for the entire period of time under study. It is revealed that the qualitative aspects of structural changes are not the same: while in China proportion of services, including the financial sector, increases, the regions of the Russia are mainly extending the proportion of extractive industries. We conclude about the possible impact of cross-border relations on the dynamics of sectoral changes in the regions of the Russia, whereas Chinese provinces are less dependent on this factor. Keywords: region, cross-border cooperation, Russia, China, structural changes. JEL Classifications: O40, O57, R11